2015
DOI: 10.1021/acs.cgd.5b01199
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Luminescence Vapochromism and Crystal-to-Amorphous-to-Crystal Transformations of Pseudopolymorphic Cu(I) Coordination Polymers

Abstract: Four solvent-responsive one-dimensional copper(I) coordination polymers (CPs), namely, {[Cu 4 I 4 L(MeCN) 2 ]·CH 2 Cl 2 } n (1), {[Cu 4 I 4 L(MeCN) 2 ]·CHCl 3 } n (2), {[Cu 4 I 4 L(MeCN) 2 ]·0.5p-xylene} n (3), and [Cu 4 I 4 L(MeCN) 2 ] n (4), were prepared by reaction of CuI with N,N′-bis[2-(cyclohexylthio)ethyl]pyromellitic diimide (L) via self-assembly under varying solvent conditions. CPs 1−4, which are pseudopolymorphic supramolecular isomers derived from solvent molecules, are composed of Cu 4 I 4 cubane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…We have reported copper(I) coordination polymers based on pyromellitic diimide derivatives (Park et al, 2011), which showed colour change owing to intermolecular halogen-interactions. In addition, we have found that reversible solvent exchange and crystal transformations were possible in the crystals (Kang et al, 2015). In an extension of previous research, we have synthesized the pyromellitic diimide in which the O atoms are replaced with S atoms, by the reaction of N,N 0 -dibenzylpyromellitic diimide with Lawesson's reagent, and report its crystal structure here.…”
Section: Chemical Contextmentioning
confidence: 86%
“…We have reported copper(I) coordination polymers based on pyromellitic diimide derivatives (Park et al, 2011), which showed colour change owing to intermolecular halogen-interactions. In addition, we have found that reversible solvent exchange and crystal transformations were possible in the crystals (Kang et al, 2015). In an extension of previous research, we have synthesized the pyromellitic diimide in which the O atoms are replaced with S atoms, by the reaction of N,N 0 -dibenzylpyromellitic diimide with Lawesson's reagent, and report its crystal structure here.…”
Section: Chemical Contextmentioning
confidence: 86%
“…evaporated to give a crude solid. The reaction mixture was then concentrated and purified by chromatography on silica gel (MeCOOEt/n-C 6 H 14 = 30/70 v/v, R F = 0.28) (Kang et al, 2015). Colourless plates were obtained by slow evaporation of a hexane solution of the title compound.…”
Section: Figurementioning
confidence: 99%
“…This is mainly because the intermolecular interactions (e. g., weak M–M interactions, metallophilic interactions, π‐stacking, and coordination modes) in transition‐metal assemblies can easily be perturbed with uptaking certain vapors into the crystal lattice, thereby inducing dramatic changes in emission color . Moreover, relevant researches evidenced that isomer conversion of metal‐complexes with remarkable emission color change can also be controlled through exposure to different vapor, which rendered a new approach to access great vapoluminescent materials . Still and all, the metal‐containing vapoluminescent compounds are generally expensive, difficult to synthesis, and environmentally unfriendly, thus limits their practical application.…”
Section: Introductionmentioning
confidence: 99%